The Choice of Peritoneal Dialysis Catheter Implantation Technique by Nephrologists - T. Yip; S. L. Lui; W. K. Lo (International Journal of Nephrology)
Peritoneal dialysis catheter (PDC) is the lifeline of peritoneal dialysis (PD) patients. One of the critical issues for successful PD is a well-functioning PDC which is timely inserted. It is the implantation technique rather than the catheter design that determines the outcome of the catheter. Dedication in acquiring the appropriate technique is vital to the success of a PD program. In this paper, we discuss the pros and cons of various techniques used for PDC implantation. A detailed description of PDC implantation by using the minilaparotomy method is presented. We strongly recommend mini-laparotomy as the method of choice for PDC implantation by nephrologists.